KPU BANDAR LAMPUNG STRATEGY: GOES TO CAMPUS, SCHOOL, AND ISLAMIC BOARDING SCHOOL TO INCREASE GEN Z AND MILLENNIAL PARTICIPATION - Rudi Santoso Rudi Santoso; Rita Zaharah (PRANATA HUKUM, 2025)
This study explores the 'Goes to Campus, School, and Islamic Boarding School' initiative by KPU Bandar Lampung aimed at enhancing political engagement among Gen Z and Millennials. By strategically targeting university students, pesantren, and high school students, KPU recognizes the unique challenges and opportunities each demographic presents in fostering a culture of civic responsibility. The effectiveness of these outreach efforts is analyzed through various methods, including interactive workshops, community engagement, and collaboration with local leaders. This paper discusses the importance of early political education, emphasizing how engaging young people in discussions about governance, democracy, and electoral processes can lead to informed voting behaviors in the future. Additionally, it addresses challenges such as political apathy and varying levels of awareness among students, proposing tailored strategies to overcome these barriers. The findings suggest that KPU's multifaceted approach not only prepares young individuals for participation in elections but also cultivates a lifelong habit of civic engagement. Ultimately, the initiative serves as a model for similar efforts across Indonesia, contributing to a more politically active and informed citizenry in the democratic landscape. The implications of these findings highlight the importance of sustained engagement and innovative outreach in promoting electoral participation among youth.